Use of meloxicam (Amelotex®) in patients with pyrophosphate arthropathy - Maksim Sergeevich Eliseev; S A Vladimirov; Maksim Sergeyevich Eliseyev; S A Vladimirov (Современная ревматология)
The paper presents the results of a trial of the efficacy and safety of the nonsteroidal anti-inflammatory drug Amelotex® (international nonproprietary name meloxicam) in patients with pyrophosphate arthropathy (PA). One-month Amelotex® therapy is shown to have a good clinical effect in patients with different forms of PA, to improve quality-of-life indices, and to show good tolerability.